2011
DOI: 10.3758/s13414-011-0196-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spatial competition between object-level representations of target and mask on object substitution masking

Abstract: One of the processes determining object substitution masking (OSM) is thought to be the spatial competition between independent object file representations of the target and mask (e.g., Kahan & Lichtman, 2006). In a series of experiments, we further examined how OSM is influenced by this spatial competition by manipulating the overlap between the surfaces created by the modal completion of the target (an outline square with a gap in one of its sides) and the mask (a four-dot mask). The results of these experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The likely answer is that OSM interferes with reentrant signaling, leaving the low-level features in the feed-forward sweep largely intact. Evidence consistent with the findings of Bouvier and Treisman has been reported by Guest et al (2011), and by Binsted et al (2007) who found that OSM occurs after the physical features of the target have been processed.…”
Section: Assumption Of Reduced Target S/n Ratiosupporting
confidence: 90%
See 1 more Smart Citation
“…The likely answer is that OSM interferes with reentrant signaling, leaving the low-level features in the feed-forward sweep largely intact. Evidence consistent with the findings of Bouvier and Treisman has been reported by Guest et al (2011), and by Binsted et al (2007) who found that OSM occurs after the physical features of the target have been processed.…”
Section: Assumption Of Reduced Target S/n Ratiosupporting
confidence: 90%
“…Increased noise at the target location can hardly be regarded as a critical determinant of OSM in Lleras and Moore’s study, simply because the target was unobscured by the trailing four-dot mask. Further evidence that OSM occurs when the mask is presented in a location other than that of the target has been reported by Jiang and Chun (2001) and by Guest et al (2011).…”
Section: Assumption Of Reduced Target S/n Ratiomentioning
confidence: 57%
“…A common alignment of the target and mask stimuli (as in the standard OSM condition) would be especially conducive to their being confused as belonging to a single object identity, as opposed to when they were spatially offset. Thus, the results of Guest et al (2011) can be taken as evidence against the notion that the target and mask representations interact at an isolated featural level (e.g., Kahan & Enns, 2010), but they are entirely consistent with the existing evidence for the object-updating account. It remains to be seen, therefore, whether there are findings in OSM that can be explained only by object substitution, and not object updating.…”
Section: Object Updating and Object Substitutionmentioning
confidence: 46%
“…It has also been suggested that the object-updating account is distinct from the object substitution account, since the former predicts that the target and mask are fused into a single object representation, whereas the latter predicts that two separate object tokens (target and mask) compete for access to consciousness Guest, Gellatly, & Pilling, 2011). Essentially, it is a question of whether the visual system encodes the target and mask as a single or two separate events.…”
Section: Object Updating and Object Substitutionmentioning
confidence: 99%
See 1 more Smart Citation